PRESENT-DAY STRESS FIELD AND RELATIVE DISPLACEMENT TENDENCY OF THE EARTH’S CRUST IN THE PARACEL ISLANDS AND ADJACENT AREA - Dung, Tran Tuan; Kulinich, R. G.; Tram, Ngo Thi Bich; Minh, Nguyen Quang; Dai, Nguyen Ba; Duong, Tran Tuan; Son, Nguyen Thai (Vietnam Journal of Marine Science and Technology, 2019)
Present-day stress filed in the Hoang Sa archipelago and adjacent areas is determined through the earthquake’s focal mechanism parameters that have been recorded during a time period of more than 100 years. The geometric parameters of the faults (such as the location, strike and dip angles as well as depth, length…) are determined by satellite-derived gravity, seismic data and stress fields. In this study, predictive determination of the magnitude and tendency of the relative displacement of the Earth’s crust is carried out by calculating and assessing the relationship between the stress fields and fault’s geometric parameters. On the basis of the Earth’s crust relative displacement, the geodynamic mechanism of the Hoang Sa archipelago and adjacent areas through the different geological periods can be rebuilt. Magnitude and tendency of the relative displacement of the Earth’s crust are represented by the color spectrum and the vector’s magnitude. Although the displacement appears in the whole region, its intensities are different in particular areas that have the faults systems with different grades